Publisher Correction: Detection of antibiotics synthetized in microfluidic picolitre-droplets by various actinobacteria. Issue 1 (December 2018) - Mahler, Lisa; Wink, Konstantin; Beulig, R.; Scherlach, Kirstin; Tovar, Miguel; Zang, Emerson; Martin, Karin; Hertweck, Christian; Belder, Detlev; Roth, Martin
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.